Pelatihan Penggunaan Website Dewan Perwakilan Daerah (DPRD) Kabupaten Nias Selatan - fau, Alwin; Ulfa, Kurnia (Jurnal Pengabdian Masyarakat Gemilang (JPMG), 2023)
The website can be used for various academic activities, especially for schools, for example conveying information related to school activities so that with this facility schools can easily disseminate information. Employees and staff at the South Nias Regency DPRD office are currently experiencing problems in using the DPRD website itself so that reporting and entry of information and news on the website which will be presented to the public are still not carried out optimally. The emergence of a misunderstanding in publishing information at the South Nias Regency DPRD office will create a problem among the public and also the DPRD itself. The research conducted can provide benefits to employees and staff at the South Nias Regency DPRD office in using and utilizing the website in conveying information to the public. On the other hand, with training on using the website, it can provide an increase in terms of service